2022
DOI: 10.5014/ajot.2022.047035
|View full text |Cite
|
Sign up to set email alerts
|

Ride-On Cars With Different Postures and Motivation in Children With Disabilities: A Randomized Controlled Trial

Abstract: Importance: A child’s independent mobility, environments, and mastery motivation are critical factors during early development. Objective: To examine the effectiveness of ride-on car (ROC) training with a standing (ROC–Stand) or a sitting posture (ROC–Sit) in enhancing children’s mastery motivation and decreasing parenting stress levels. Design: Randomized controlled trial (RCT) with a multiple pretest–posttest design. Setting: Hospital-based environment in northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The study was part of a larger randomized controlled trial (RCT) that investigated the effectiveness of ROC training in young children with motor delays, either in standing or sitting postures. 7,15 Study approval (103-7368A8) was obtained from the Chang Gung Medical Foundation Institutional Review Board, and caregivers provided written informed consent prior to data collection. Participants were enrolled in November 2015, and the study was completed in October 2019.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study was part of a larger randomized controlled trial (RCT) that investigated the effectiveness of ROC training in young children with motor delays, either in standing or sitting postures. 7,15 Study approval (103-7368A8) was obtained from the Chang Gung Medical Foundation Institutional Review Board, and caregivers provided written informed consent prior to data collection. Participants were enrolled in November 2015, and the study was completed in October 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence: There is a growing recognition among parents and clinicians of the potential benefits of early power mobility training for children who have motor delays. 6,7 Previous studies have indicated that caregivers commonly perceive device-and environmental-related barriers as the most significant obstacles to successfully using a ride-on car (ROC) in home environments. 10,11 The researchers have suggested that appropriate adjustments and sufficient support from therapists through practical strategies could address most barriers.…”
Section: What This Evidence Adds Amentioning
confidence: 99%
See 3 more Smart Citations